Lexical competition influences correct and incorrect visual word recognition. Issue 5 (May 2023) - Gregg, Julie; Inhoff, Albrecht W; Li, Xingshan
A growing body of research suggests that visual word recognition is error-prone, and that errors may contribute to inhibitory neighbour frequency effects in word identification and reading. The present study used the neighbourhood frequency effect to examine the relationship between lexical competition and error making during visual word recognition. A novel adaptation of the visual world paradigm (VWP) was used, in which participants selected a briefly presented printed target word from an array containing the target, its higher- or lower-frequency neighbour, an orthographic onset competitor, and an orthographically unrelated distractor word. Analyses of the visual inspection of the arrays suggested that lexical competition occurred when words were correctly identified, as competitors were preferentially viewed as a function of their orthographic similarity with the target, and higher-frequency neighbours were preferentially viewed over lower-frequency neighbours. Orthographic similarity and neighbour frequency also influenced error making. Targets were often mistaken for their neighbours, and these errors were more common for targets with higher-frequency neighbours. The time course of target and neighbour viewing for error trials also provided preliminary evidence for two kinds of errors: early-occurring, perceptual errors and later-occurring selection errors that resulted from unsuccessfully resolved lexical competition. Together, these findings suggest that neighbour frequency effects reflect the contribution of both general lexical competition and occasional errors.